1993
DOI: 10.1007/bf01839162
|View full text |Cite
|
Sign up to set email alerts
|

Type, diameter and distribution of fibres in some respiratory and abdominal muscles of the goat

Abstract: This study was designed to determine the histochemical properties, size and composition of fibres in the diaphragm, intercostal and abdominal muscles of goats to clarify whether reported similarities in respiratory muscle physiology between goats and humans have a structural basis. Serial sections (10 microns) of muscular tissue from adult female goats were stained for myosin adenosine triphosphatase and reduced nicotinamide adenine dinucleotide dehydrogenase-tetrazolium reductase activities; the fibres were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The type I fibers diameter without stimulation was slightly smaller than the reported diameters of the abdominal wall [11]. The type I fiber diameter decreased in the two goats, whereas the type II fibers had the same diameter.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The type I fibers diameter without stimulation was slightly smaller than the reported diameters of the abdominal wall [11]. The type I fiber diameter decreased in the two goats, whereas the type II fibers had the same diameter.…”
Section: Discussionmentioning
confidence: 56%
“…Others reported comparable percentages of type I fibers of the goat latissimus dorsi muscles [10], and increases of type I fibers of the abdominal wall muscles [11] at 20-30%. Since these muscles have a function comparable to that of the gracilis muscle, the observed percentages seem representative.…”
Section: Discussionmentioning
confidence: 89%
“…Another quadrupedal that had its rectus abdominis muscle studied was the sheep, Ibebunjo (1993); in which the 3 fiber types (I, IIA, and IIB) were found in equal proportion, different from the data found for the tufted capuchin monkey. In terms of frequency, this research found a predominance for fast twitch fibers in all 4 regions, as observed by Ibejunjo, who analyzed abdominal muscles in sheep.…”
Section: Discussionmentioning
confidence: 66%
“…In goats, 58.9% of fibers present are Type I, and 41.1% are Type II. In humans, more than 50% of these fibers are Type I (Ibebunjo 1993).…”
Section: Resultsmentioning
confidence: 99%